2021
DOI: 10.3389/fnagi.2021.772278
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrases as Potential Targets Against Neurovascular Unit Dysfunction in Alzheimer’s Disease and Stroke

Abstract: The Neurovascular Unit (NVU) is an important multicellular structure of the central nervous system (CNS), which participates in the regulation of cerebral blood flow (CBF), delivery of oxygen and nutrients, immunological surveillance, clearance, barrier functions, and CNS homeostasis. Stroke and Alzheimer Disease (AD) are two pathologies with extensive NVU dysfunction. The cell types of the NVU change in both structure and function following an ischemic insult and during the development of AD pathology. Stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 225 publications
(531 reference statements)
5
43
0
Order By: Relevance
“…Additionally, while untreated TgSwDI mice showed significant vasoconstriction in DG and cortex, vessel width in CAI-treated mice was restored to WT levels. If on one hand these results corroborate the impact of CAA on EC degeneration and blood vessel dysfunction, as observed in AD subjects [52], on the other hand they confirm that CAIs may be able to regulate cerebral vessel tone, possibly by both reducing EC mitochondrial stress and ROS production [38][39][40]44],…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Additionally, while untreated TgSwDI mice showed significant vasoconstriction in DG and cortex, vessel width in CAI-treated mice was restored to WT levels. If on one hand these results corroborate the impact of CAA on EC degeneration and blood vessel dysfunction, as observed in AD subjects [52], on the other hand they confirm that CAIs may be able to regulate cerebral vessel tone, possibly by both reducing EC mitochondrial stress and ROS production [38][39][40]44],…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, arterial pulsation, which is important for multiple clearance mechanisms including IPAD [26, 136], can also be improved by CAIs [44, 56], suggesting that ATZ and MTZ could exert additional positive effects by improving vascular smooth muscle cell tone and function, which is currently the subject of further studies by our group.…”
Section: Discussionmentioning
confidence: 99%
“…CA inhibitors can be used for the development of anti-infective agents (CAs are responsible for the survival and virulence of certain pathogens) [ 38 ], for the treatment of glaucoma [ 39 ], cerebral ischemia [ 40 ], rheumatoid arthritis [ 41 ], obesity [ 42 ], neuropathic pain [ 43 ], epilepsy [ 44 ], or cancer [ 45 ]; in this context, it is important to highlight that CA IX and XII are overexpressed in numerous tumors, where they control the microenvironment pH (acidification of the extracellular medium) [ 46 ] and certain metabolic processes connected to tumor growth and metastasis [ 47 ]. Recent evidence also correlates CA inhibition with neuroprotective effects in Alzheimer’s disease [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“… 26 The unexpected and novel application of CAIs in synaptic transformation and attentional gating of memory is quite appreciating in the treatment of Alzheimer’s disease. 27 …”
Section: Introductionmentioning
confidence: 99%
“…CAs are committed as attractive targets for drug design to cure therapeutic diseases like acid–base disequilibria, epilepsy, glaucoma, cancer, osteoporosis and other neuromuscular disorders, edema, altitude sickness, and obesity. , Recent studies have shown the role of CA inhibitors (CAIs) as a therapeutic hit for other diseases like neuropathic pain, cerebral ischemia, and tumor . The unexpected and novel application of CAIs in synaptic transformation and attentional gating of memory is quite appreciating in the treatment of Alzheimer’s disease …”
Section: Introductionmentioning
confidence: 99%